Disclosed Industry Funding Does Not Increase Positive Outcomes in Studies on Suture Button Fixation for Ankle Syndesmotic Injuries: A Systematic Review - Cailan L. Feingold BS; Eric H. Lin BA; Ajith K. Subhash MD; Samuel C. Tercyak BS; Aidan A. Jagasia BS; Eric W. Tan MD; Alexander B. Peterson MD; Joseph N. Liu MD (Foot & Ankle Orthopaedics)
Background: Industry funding can increase the likelihood of positive outcomes. This study sought to investigate whether industry funding or conflicts of interest (COI) for studies investigating suture button fixation devices for ankle syndesmosis injuries influenced outcomes. Methods: PubMed, Scopus, and Embase were queried for studies investigating suture button fixation devices for the ankle. Included studies investigated suture button fixation devices for the ankle and reported funding or COI. Excluded studies were systematic reviews, meta-analyses, and case reports. Outcomes were categorized into “positive” if the null hypothesis was rejected or outcomes favored the implant, “neutral” if the null hypothesis was confirmed, or “negative” if the result was unfavorable toward the implant. Studies were grouped into industry-funded, nonfunded, and “other” funding, including specialty societies, National Institutes of Health (NIH), and grants. Studies were also grouped by the presence or absence of COI. Chi-squared test was used to test for significance defined as P  <.05. Results: A total of 112 studies were included for analysis. Of these, 19 (17%) were industry-funded, 21 (19%) had other funding sources, and 72 (64%) were nonfunded. The proportion of studies with positive outcomes was 48% in industry-funded studies, 63% in studies with other funding sources, and 65% in nonfunded studies. There was no significant association between funding source and outcome ( P  = .063). A COI was present in 42 studies (37.5%), and no COI was present in 70 studies (62.5%). The proportion of positive studies in those with a COI was 52%, whereas in studies without a COI, it was 67%. Positive studies were significantly associated with studies without COI ( P  = .003). Conclusion: Industry funding and COI was not found to be associated with an increased likelihood of positive outcome reporting in studies on suture-button fixation for ankle syndesmostic injuries; we found in this review that positive outcomes are more likely in studies without COI.